Keterlibatan Warga Negara Dalam Forum Kewarganegaraan Lingkungan (FKL) Di Kota Banjarmasin - Reja Fahlevi; Fathul Jannah; Nurul Huda (University of Muhammadiyah Malang, 2023)
The purpose of this study was to determine citizen involvement in the Environmental Citizenship Forum (FKL) in Banjarmasin City. This research uses a qualitative approach, with a descriptive research method. This research was conducted at the Environmental Citizenship Forum (FKL) in Banjarmasin City which is a Youth Organization (OKP) under the auspices of the KNPI in South Kalimantan Province. The results of the Citizen Engagement Research conducted by the Environmental Citizenship Forum (FKL) in the City of Banjarmasin are in two stages, namely socialization and participation. The socialization they carried out was by socializing Banjarmasin City Regional Regulation No. 21 of 2011 concerning Clean Waste Management which regulates the Rights and Obligations of Citizens in protecting and preserving the environment in several High Schools (SMA) in Banjarmasin City. Their participation is carrying out the